2021
DOI: 10.3727/154427220x16092157169853
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Ecotourism and Conservation Measures in Protected Areas on Local Communities in Cameroon

Abstract: The growth of ecotourism has an impact on the livelihoods of people living within and adjacent to protected areas, where ecotourism activities often take place. In some cases, evolving ecotourism has compromised the ability of locals to sustain and diversify their livelihoods. The aim of this study was to examine the impact of ecotourism and conservation measures implemented in protected areas in Cameroon on local communities residing either within or in close proximity to them. The study employed a mixed-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Tourism and modernization theory, originating in the mid-20th century, posit that tourism drives societal modernization . Tourism and dependency theory, emerging in the 1960s, examines the potential pitfalls of tourism, including economic dependency (Harilal et al, 2021). The alternative development theory of tourism was born out of critiques of mainstream tourism paradigms, emphasizing sustainable development and community empowerment (Dick, 2021)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Tourism and modernization theory, originating in the mid-20th century, posit that tourism drives societal modernization . Tourism and dependency theory, emerging in the 1960s, examines the potential pitfalls of tourism, including economic dependency (Harilal et al, 2021). The alternative development theory of tourism was born out of critiques of mainstream tourism paradigms, emphasizing sustainable development and community empowerment (Dick, 2021)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They are important determinants contributing to tourist satisfaction at a destination (Pekerşen & Kaplan, 2023). The impact of tourism development on the local community has been the subject of extensive research (Harilal et al, 2021). As tourism develops, locals become more aware of its economic benefits (Beritelli et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ecotourism development has got widespread attention from both academic researchers and industry practitioners (KC et al , 2021; Kalyar et al , 2021; Molina-Collado et al , 2022; Pablo-Cea et al , 2021; Vyasha et al , 2021). Studies have also examined ecotourism knowledge of the tourists to check their travel activities in particular (Duong et al , 2021; Khanh, 2020; Li et al , 2021; Oviedo-García et al , 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The relationship between community development, tourism and conservation are complex and dynamic. Several studies have found that to meet the growing demand for ecotourism, many sites have been converted to ecotourism keeping the objectives aside (Chowdhury and Maiti, 2016; Sanchez, 2018; Stronza et al , 2019; Vyasha et al , 2021; Wishitemi et al , 2015). Sometimes it is mere green washing at the operational level (Ashok et al , 2019; Cabral and Dhar, 2020).…”
Section: Introductionmentioning
confidence: 99%